Implementasi Qana’ah dengan FoMO (Fear of Missing Out) di TikTok Shop pada Duta Generasi Berencana UIN Raden Intan Lampung 2024 - Firmansyah, Alfi; Putra, Andi Eka; Ismail, Moh. (Prodi Tasawuf dan Psikoterapi Fakultas Usluhuddin dan Dakwah, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, 2025)
This study aims to prove that applying the nature of Qana’ah in a Generasi Berencana Ambassador is important because it can reduce the negative impact of FoMO behavior. This research method uses a descriptive qualitative method that contains data excerpts that provide an overview of the presentation of the report with the purposive sampling research method. The informants used in this study consisted of 10 Generasi Berencana Ambassadors with 6 women and 4 men. The researcher conducts interviews and observations and then analyzes the results of the interviews and observations. The results of the research obtained by the Qana’ah researcher are a solution to the problems that occurred in the 2024 Generation Planning Ambassador of UIN Raden Intan Lampung in the FoMO phenomenon. The phenomenon that is happening today is about the Fear of Missing the Moment (FoMO) experienced by the Generation Planning Ambassador of UIN Raden Intan Lampung 2024. This is a quite serious problem considering the impact of Fear Of Missing Out causes them to be anxious about missing the moment of new things that are trending at this time. With qana’ah, Generasi Berencana Ambassadors feel satisfied with what they already have and enjoy the blessings that have been given by Allah Swt. to him.